Design Aids for Stiffened Composite Shells with Cutouts - Sahoo, Sarmila; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2017)
This book focuses on the free vibrations of graphite-epoxy laminated composite stiffened shells with cutout both in terms of the natural frequencies and mode shapes. The dynamic analysis of shell structures, which may have complex geometry and arbitrary loading and boundary conditions, is solved efficiently by the finite element method, even including cutouts in shells. The results may be readily used by practicing engineers dealing with stiffened composite shells with cutouts. Several shell forms viz. cylindrical shell, hypar shell, conoidal shell, spherical shell, saddle shell, hyperbolic paraboloidal shell and elliptic paraboloidal shell are considered in the book. The dynamic characteristics of stiffened composite shells with cutout are described in terms of the natural frequency and mode shapes. The size of the cutouts and their positions with respect to the shell centre are varied for different edge constraints of cross-ply and angle-ply laminated composite shells. The effects of these parametric variations on the fundamental frequencies and mode shapes are considered in detail. The information regarding the behavior of stiffened shells with cutouts for a wide spectrum of eccentricity and boundary conditions for cross ply and angle ply shells may be used as design aids for structural engineers. The book is a significant contribution to the existing literature from the point of view of both industrial importance and academic interest.
Keywords: Civil Engineering; Solid Mechanics; Building Materials; Ceramics, Glass, Composites, Natural Materials